ROLE OF POLYAMINES IN INHIBITION OF ETHYLENE BIOSYNTHESIS AND THEIR EFFECTS ON RICE ANTHER CULTURE DEVELOPMENT - Iswari S. Dewi; Bambang S. Purwoko (Indonesian Journal of Agricultural Science, 2008)
The polyamines such as putrescine, spermidine, and spermine were reported to increase green plant regeneration in rice anther culture. Low response of anther culture of rice sub-species indica may be improved with the addition of putrescine in the culture media. Four experiments were conducted to study the role of polyamines in inhibition of ethylene biosynthesis and their effects on rice anther culture development. Anthers of two subspecies of rice, indica (IR64, Krowal, Jatiluhur) and japonica (Taipei 309) were cultured onto media supplemented with putrescine (N6P) and without putrescine (N6). Youngpanicles containing the anthers at mid-to-late nucleate microspores were cold pretreated at 5 + 2°C and incubated in the dark for 8 days before the anthers were cultured. Resultsshowed that medium without putrescine produced an earlier senescence of indica rice anther than that of japonica. The addition of 10-3 M putrescine into the culture media inhibited ethylene biosynthesis as anther senescence delayed, increased the three polyamines contents, and decreased the ACC content as well as ACC oxydase activity in anther-derived calli. In the anther and anther-derived calli of subspecies indica, the totalpolyamines content was lower (10.14 nM g-1 anther and 8.48 nM g-1 calli) than that of subspecies japonica (12.61 nM g-1 anther and 10.16 nM g-1 calli), whereas the ethylene production was higher (32.31 nM g-1 anther and 2.48 nM g-1 calli) than the japonica (31.68 nM g-1 anther and 1.76 nM g-1 calli). This study suggests that application of 10-3 M putrescine in anther culture of rice subspecies indica improves androgenesis by inhibitingearly senescence of cultured anthers and enhancing embryo or callus formation from microspores.